EPISTEMOLOGI PENCAPAIAN ILMU AL-GHAZALI - Albadri Albadri (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2020)
The basic nature of science is to develop, even though it is still necessary to develop a science strategy so that science is in accordance with the existing objectives and also the rules of applying science. Al-Ghazali divided the principles of the application of science into seven and the strategy for developing science into six strategies. This cannot be separated from the responsibility of science, scientists, and also the community. Because all three are interrelated. Of the six strategies for developing knowledge, basically, all the sciences already have those strategies.